Teaching the Procedures and Routines to Manage Kids at the Kindergarten - Grediana Rumlus (Green Publisher Indonesia, 2021)
Teaching the routines and procedure is the way to form good skill and behaviour at the early of education.The habit and routine are formed from home.Classroom routines and procedures is a set to maintain order in the classroom. When entering the classroom, students will enter in a quiet manner. They will sit at their assigned desk and have all material ready to begin on required work. Once the bell rings and the door is closed, students will be seated and working. Tardiness is unacceptable and if the student receives more than three unexcused tardies per 2 months. The princinple will disscused it with their parents. Also, students should not be more than three minutes late to class. Students will maximize their learning time by staying on task and following directions, and remain seated unless instructed to do otherwise. There will always be work available for the student to complete. Being patient, which is also the rule, students must follow all the rules at school. They all should be actively listening to one another and learning. The last and most important rule is to be polite. The purpose of this research is for ways to shape good skills and behaviors at the beginning of education. There are also procedures that can be achieved in carrying out early childhood learning for Jamal in his book Strategic Management of Early Childhood Learning, including global ordinances (Ganze ordinances), trial procedure, procedures for learning while doing, procedures for home schooling groups and procedures for Glenn Doman